Training For Making Handsanitizer From Betel Leaf Extract and Lime Oranges in Smp Negeri 2 Na Ix-X Sumberjo, Labuhanbatu Utara Regency - Bella Anggelia; Elvina Elvina; Novrihan Leily Nasution (International Journal Of Community Service, 2022)
The purpose of community service is to overcome the demand for hand sanitizers during the current covid-19 pandemic. To overcome the limited supply of Handsanitizer, the author took the initiative to make it from natural ingredients from betel leaf extract andlime. Choosing to use natural ingredients that are easily found such as betel leaf and lime, because these materials are very easy to find in the neighborhood so it can make it easier to carry out the training. The location of this community service is at SMP Negeri 2 Na IX-X Sumberjo. The target of PKM this time is class IX-1 students, totaling 27 students. The method used is the method of observation, discussion and training. The main purpose of this PKM is to provide information to students of SMP Negeri 2 NA XI-X Sumberjo how to make natural hand sanitizer. And use the materials around them to make a natural hand sanitizer without alcohol.